An Analysis of Gandhi's Constructive Program Based on Galtung's Theories - Dillon, Amy (Université Saint-Paul / Saint Paul University, 2016)
Mohandas Gandhi emphasized the importance of his constructive program as nonviolent action. This thesis examines the constructive program through the lens of Johan Galtung’s theories. The analysis illustrates the cultural and structural violence to which the program was responsive. Two examples include exploitation through industrialization, and repression through the custom of untouchability. Both examples were supported by cultural violence in the idea of superiority and inferiority between groups of peoples. The analysis demonstrates that the constructive program established cultures and structures that support cycles of nonviolence in response to existing cycles of violence. Two forms of cultural nonviolence expressed were personal social responsibility, and unity of humanity. Two forms of structural nonviolence established were nonviolent self-sufficiency with dignity, and nonviolent education. This thesis shows that Gandhi’s constructive program demonstrated eight qualities: intentionally nonviolent, voluntary, inclusive, autonomous, responsive to cultural and structural violence, self-reinforcing, context-specific, and comprehensive.
Keywords: nonviolence; structural; cultural; constructive; peace; violence